A systematic review and Bayesian meta-analysis of the antibiotic treatment courses in AECOPD - Yu, Haichuan; Lei, Ting; Su, Xiaojie; Zhang, Lu; Feng, Zhouzhou; Chen, Xinlong; Liu, Jian (Frontiers in Pharmacology, 2023)
Background: No consensus exists on the antibiotic treatment course for patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Former studies indicate that shorter courses might have the same efficacy with fewer adverse events, which is inconsistent with guidelines and general practice. Existing evidence allows us to conduct a systematic review and Bayesian analysis on this topic. Methods: Four databases were searched from their inception to January 5, 2023. All statistical estimations were performed using R. "Gemtc" was the core package of analysis. CINeMA was used to assess the grade of confidence of the results. Results: Fourteen studies were included in the Bayesian meta-analysis. No difference in the clinical success rate of antibiotic treatment was observed from a super short course (1–3 days) to a long course (≥10 days). Considering the adverse events, the short course (4–6 days) might be the safest. The majority of results are of high or moderate confidence grade. Conclusion: Short course might cause the fewest adverse events. The clinical efficacy of antibiotics might not depend on the course length. Undeniably, more systematic explorations are warranted to investigate the clinical application of a shorter course of antibiotic treatment.